The Strategic Role of the Commercial Court in Resolving Digital Company Bankruptcy Disputes - Rizkia, Nanda Dwi; Fardiansyah, Hardi; Danil, Danil; Suryani, Lilis; Yuliana, Tora; Riverra, Kevin M (Faculty of Law, Universitas Pattimura, 2025)
Introduction: The digital economy has transformed legal structures, especially in insolvency law, where digital companies often treat personal data as a core asset. However, Law Number 37 of 2004 on Bankruptcy and Suspension of Debt Payment Obligations lacks specific provisions regarding personal data, while Law Number 27 of 2022 on Personal Data Protection does not address how data should be treated in bankruptcy. This regulatory gap risks the exploitation of personal data by creditors or curators, potentially violating constitutional rights.Purposes of the Research: This study aims to examine the legal consequences of the absence of clear regulations on personal data in bankruptcy cases and propose legal solutions to protect data subjects’ rights within digital insolvency proceedings.Methods of the Research: The research employs a normative juridical approach, combining statutory and conceptual analyses. It examines relevant Indonesian laws and draws comparisons with the European Union’s General Data Protection Regulation (GDPR) to understand international best practices. Legal materials are analyzed qualitatively.Results Main Findings of the Research: The study proposes recognizing personal data as a sui generis legal object in bankruptcy proceedings, requiring distinct legal treatment and safeguards. It highlights the role of the Commercial Court in protecting data subjects’ rights and suggests amending the UUK-PKPU, issuing Supreme Court guidelines, and promoting interagency coordination. This research contributes a normative model to integrate personal data protection within Indonesia’s digital insolvency framework, ensuring constitutional rights remain upheld in the digital era.